Comparative pharmacodynamics of four different carbapenems in combination with polymyxin B against carbapenem-resistant Acinetobacter baumannii - Lenhard, Justin R. (Int J Antimicrob Agents, 2016)
The objective of this study was to determine the comparative pharmacodynamics of four different carbapenems in combination with polymyxin B (PMB) against carbapenem-resistant Acinetobacter baumannii isolates using time–kill experiments at two different inocula. Two A. baumannii strains (03-149-1 and N16870) with carbapenem minimum inhibitory concentrations (MICs) ranging from 8 to 64 mg/L were investigated in 48-h time–kill experiments using starting inocula of 10(6) CFU/mL and 10(8) CFU/mL. Concentration arrays of ertapenem, doripenem, meropenem and imipenem at 0.25×, 0.5×, 1×, 1.5× and 2× published maximum serum concentration (C(max)) values (C(max) concentrations of 12, 21, 48 and 60 mg/L, respectively) were investigated in the presence of 1.5 mg/L PMB. Use of carbapenems without PMB resulted in drastic re-growth. All carbapenem combinations were able to achieve a ≥3 log(10) CFU/mL reduction by 4 h against both strains at 10(6) CFU/mL, whereas maximum reductions against strain 03-149-1 at 10(8) CFU/mL were 1.0, 3.2, 2.2 and 3.3 log(10) CFU/mL for ertapenem, doripenem, meropenem and imipenem, respectively. None of the combinations were capable of reducing 10(8) CFU/mL of N16870 by ≥2 log(10) CFU/mL. Ertapenem combinations consistently displayed the least activity, whereas doripenem, meropenem and imipenem combinations had similar activities that were poorly predicted by carbapenem MICs. As doripenem, meropenem, or imipenem displayed similar pharmacodyanmics in combination, the decision of which carbapenem to use in combination with PMB may be based on toxicodynamic profiles if drastic discordance in MICs is not present.